PENGEMBANGAN MODUL IPS BERBASIS KETERAMPILAN SOSIAL - Juwariyah Juwariyah; Pargito Pargito; Herpratiwi Herpratiwi (Faculty of Teacher Training and Education, University of Lampung, 2013)
Research and development is motivated by text books is difficult to understand its content, and the need for students' social skills. Research for Development aims to produce IPS module-based social skills and to analyze the effectiveness of social skills-based IPS module. This study is a research development (R D) with a modified Borg and Gall withthe development of Dick and Carey module design. The effectiveness of the product obtained using experimental test of pre-test and post-test. Pre-test and post-test were analyzed using test and comparison of normalized gain. The results of this research is the creation of a social skills-based module products. IPS module - based social skill. Obtaining response sappropriate and good for development. The module effectively demonstrated through test effectiveness by comparing normalized gain value indicatesa higher efficacy with the acquisition value gain of 0.700Keywords: module, IPS, social skills